Identification of important plant areas in the Mountainous Eastern Karatau (Mangystau) - Adamzhanova, Zh.; Mukhtubayeva, S.; Duisenova, N.; Lukmanov, A. (NLC “Karaganda National Research University named after аcademician Ye.A. Buketov”, 2025)
The identification of Important Plant Areas (IPAs), which are of particular significance for the conservation of biological diversity, is one of the international programs implemented under the Convention on Biological Diversity. The aim of this study was to identify IPAs in the Eastern Karatau Mountains. Field research was conducted using the traditional route reconnaissance method, covering the most diverse biotopes (landscape and ecological conditions) and their characteristic phytocoenoses. The vegetation cover of the identified areas was studied using standard geobotanical methods, including the description of plant communities, as well as the assessment of species diversity and vegetation condition. The flora of the Mangystau Region is characterized by a relatively low level of species diversity, and the vegetation cover is typical of desert regions. Based on criteria A–C, eight IPAs were identified: Kurkeruek, Kirezhyk Zheke, Eskildi Aday, Shili, Kaskyr Sai, Kaskyr Sai 2, Bakshy, and Agashty. The locations of ten species with IUCN conservation statuses 2(U), 3(R), and 4(I) were recorded: Armeniaca vulgaris, Tulipa sogdiana, Capparis herbacea, Crambe edentula, Ephedra aurantiaca, Onosma staminea, Rhamnus sintenisii, Rubus caesius, Verbascum blattaria, and Crataegus ambigua. For each Important Plant Area, a passport was compiled, threats to vegetation were identified, and recommendations for biodiversity conservation were developed.
Keywords: flora; Eastern Karatau Mountains; rare; endangered species; endemics; Red Book of Kazakhstan; important plant areas